Pengaruh Strategi Pemasaran Pendidikan Terhadap Citra Lembaga Pendidikan Islam di MTs Sepatan - Diniyati Hasanah; Anis Zohriah; Machdum Bahtiar; Anis Fauzi (Journal on Education, 2023)
The positive image of educational institutions requires marketing. If an educational institution has a positive image in the eyes of the public, it will be more competent than other schools. Management with a good strategy is the main emphasis for the implementation of the entire existing education system, especially in the education sector. The purpose of this study is to determine the effect of marketing strategy. the influence of educational marketing strategies on the image of Islamic education institutions at MTs Sepatan. The method used is descriptive with quantitative analysis using data analysis techniques in the form of simple linear regression. Based on the results of the study, it shows that the marketing strategy is explained by 97% by the image of the institution, while 3% is explained by other factors not examined in this study. The marketing strategy partially has a significant effect on the image of the MTs Sepatan institution. The direction of influence of the marketing strategy on the image of the institution is positive, which means that the higher the marketing strategy, the higher the image of the institution, and vice versa. If the marketing strategy is lower then the image of the institution will decrease.